Revealing statistical principles - Lindsey, James K. (London : Arnold ; New York : Oxford University Press, 1999)
This book aims to engender the reader with an understanding of the principles behind the statistics, thus demystifying a subject which is often feared.
Includes bibliographical references and index.
mf 25/01/2019
Loans
Keywords: Statistics